Characterization and Production of Goat Milk Kefir-Peptide on Triglyceride Synthesis of Cell Model of 3T3-L1 - Dian Laksamana Hati; Sri Andarini; Dian Handayani; Djalal Rosyidi; Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2023)
Goat milk kefir (GMK) refers to fermented products, generated through fermenting milk with microbial culture called kefir grains. Prior studies have reported the changes in kefir quality properties during aging process in which fermentation continues, resulting in changes of the peptide content. This research aims to investigate the effect of aging time on GMK–peptide characteristics to inhibite triglyceride syntheses on cells model of 3T3-L1. In this study, GMK were stored at 4 ± 1 oC for 0, 2, 4, 6 and 8 weeks, respectively. The protein profile was characterizedby implementing SDS-PAGE. The result of experiment indicated no protein degradation during the 6 weeks of aging period particularly for high molecular weight at 84 kDa, 80 kDa and 65 kDa. The GMK-supernatant from 8 weeks storage was performed by applying ultrafiltration membrane cut off < 30 kDa (UFC8 030.08). GMK-filtrate fractions (GMK-peptide) was collected as peptides. After 8 weeks of aging period, kefir protein profile was found to consist of peptide fractions and amino acid. The proteolytic activity of kefir grain increased linearly along with aging time (0-8 weeks). During aging period, the proteolytic activity of grain kefir released peptides and amino acid. In particular, the antioxidant activities were found significantly different (p<0.05) during aging periods. The antioxidant activities of GMK-peptide increased along with the elevating peptide concentration, from 3.30 % to 55.73%, with derivate by GMK-peptides of 2.75 – 10.39 mg/ml. Obesity associated with adipocyte hypertrophy occurred when TG accumulation.GMK-peptide of 100 mg/ml indicated the lowest TG level (2.00 ± 0.03 mg/dl). This finding was in line with the inhibition of TG synthesis (61.14 ± 3.26 %). However, GMK-peptide contained antioxidant potency due to may be corelated with decreasing TG synthesis.The study thus suggested the important role of kefir to prolong aging in generating higher peptide bioactive as antioxidant and inhibition of TG synthesis of cell model of 3T3-L1